2022
DOI: 10.1111/jocn.16418
|View full text |Cite
|
Sign up to set email alerts
|

Participation in daily activities after acute illness hospitalization among high‐functioning older adults: a qualitative study

Abstract: Aims and objectives To describe high‐functioning older adults' experiences of participation in daily activities and perceived barriers and facilitators to participation one‐ and 3‐months post‐acute hospitalization. Background Older adults discharged after acute illness hospitalization are at risk for functional decline and adverse health outcomes. Yet, little is known about the subjective experience of resuming participation in meaningful activities beyond the immediate post‐discharge period among high‐functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 62 publications
1
16
2
Order By: Relevance
“…Recovering from acute hospitalization can pose significant challenges for older adults as they strive to readjust to their regular activities and restore their previous level of functioning 1–3 . About 30% to 60% of adults 65 years of age and older experience functional decline (a decrease in the ability to engage in activities of daily living) during their hospital stay, associated with prolonged periods of inactivity during hospitalization 4–6 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recovering from acute hospitalization can pose significant challenges for older adults as they strive to readjust to their regular activities and restore their previous level of functioning 1–3 . About 30% to 60% of adults 65 years of age and older experience functional decline (a decrease in the ability to engage in activities of daily living) during their hospital stay, associated with prolonged periods of inactivity during hospitalization 4–6 .…”
mentioning
confidence: 99%
“…Physical activity has several benefits for older adults as it can improve physical and cognitive function, boost mental health, reduce falls, prevent delirium, and lower the risk of disease in older adults 12,13 . Despite the established benefits of physical activity, low physical activity is common in older adults after hospitalization from an acute illness 1,3,14 . Prior work has shown that low levels of physical activity in older adults can persist for 6 months following hospitalization 15 .…”
mentioning
confidence: 99%
See 3 more Smart Citations